2021
DOI: 10.1021/acs.jpclett.0c03492
|View full text |Cite
|
Sign up to set email alerts
|

Osmoprotectant Coated Thermostable Gold Nanoparticles Efficiently Restrict Temperature-Induced Amyloid Aggregation of Insulin

Abstract: Naturally occurring osmoprotectants are known to prevent aggregation of proteins under various stress factors including extreme pH and elevated temperature conditions. Here, we synthesized gold nanoparticles coated with selected osmolytes (proline, hydroxyproline, and glycine) and examined their effect on temperature-induced amyloid-formation of insulin hormone. These uniform, thermostable, and hemocompatible gold nanoparticles were capable of inhibiting both spontaneous and seed-induced amyloid aggregation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 59 publications
6
35
0
Order By: Relevance
“…Under temperature-induced aggregation conditions, the population of aggregation-prone intermediate structures increases, and due to this reason, the self-assembly process is initiated. 25,38,51 In this study, the interaction between the plumbagin molecule and the proteins (BSA and insulin) seems to stabilize their native structures (Figure 1e−h and Figure 3d−f). Thermal unfolding experiments confirmed that the T m of insulin was increased by ∼3.8 °C in the presence of plumbagin (Figure 1h).…”
Section: ■ Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Under temperature-induced aggregation conditions, the population of aggregation-prone intermediate structures increases, and due to this reason, the self-assembly process is initiated. 25,38,51 In this study, the interaction between the plumbagin molecule and the proteins (BSA and insulin) seems to stabilize their native structures (Figure 1e−h and Figure 3d−f). Thermal unfolding experiments confirmed that the T m of insulin was increased by ∼3.8 °C in the presence of plumbagin (Figure 1h).…”
Section: ■ Discussionmentioning
confidence: 58%
“…To further understand the potential of plumbagin to stabilize the native structure of insulin, fluorescence experiments were performed on guanidine hydrochloride (GnHCl)-treated insulin samples. 38 The control insulin sample showed a gradual increase in the fluorescence emission (λ max = 305 nm) of insulin with an increasing GnHCl concentration (Figure 1i), suggesting an unfolding event of the folded insulin conformation via chemical denaturation. 16 However, the extent of chemical denaturation was substantially reduced in the presence of plumbagin (Figure 1j,k), which reflects that the plumbagin molecule can stabilize the folded structure of native insulin.…”
Section: ■ Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Since L-Pro is a potent and non-toxic chemical chaperone, its intracellular accumulation could be an evolutionarily conserved response aimed at inhibiting the formation of unfolded/misfolded protein aggregates. Indeed, hemocompatible gold nanoparticles coated with L-Pro inhibit both collagen fibril formation (Anand et al, 2017) and insulin aggregation (Prajapati et al, 2021), and could provide a basis for creating antifibrotic and antiamyloid formulations.…”
Section: Discussionmentioning
confidence: 99%